The use of outcome data from quality registries to learn and improve; a Dutch nationwide quantitative analysis in five disease areas - Stacey R. Slingerland; Lise A. M. Moers; Niki M. Medendorp; Paul B. van der Nat; Lineke Derks; Marijke J. C. Timmermans; Nicolette de Keizer; Marc ten Dam; Geke Denissen; Dennis van Veghel (BMC Health Services Research)
Abstract Background Clinical quality registries (CQR) aid in measuring, collecting and monitoring outcome data but it is still unknown how these data are used by hospitals to improve the quality of care. This study assessed the current state of outcome-based quality improvement in the Netherlands in 2022 based on data from multiple disease areas and CQRs; cardiothoracic surgery (Netherlands Heart Registration [NHR]), cardiology (NHR), nephrology, (Nefrovision), intensive care (National Intensive Care Evaluation [NICE]), and orthopaedic surgery (Dutch Arthroplasty Register [LROI]). Methods & results The Health Outcomes Management Evaluation (HOME) model was used to assess the current state of outcome-based quality improvement. A questionnaire with 36 questions was sent to healthcare departments of the six disease areas in participating hospitals within five quality registrations in the Netherlands. In total, 124 responses were received; 20 within cardiology, 12 within cardiothoracic surgery, 30 within nephrology, 35 within intensive care and 27 within orthopaedic surgery. Results showed outcome measures were actively used to improve the quality of care, several improvement initiatives were implemented, but outcomes were not always monitored regularly. Results differed between hospitals, but differences were limited between disease areas. Conclusion The current state of outcome-based quality improvement in all five disease areas is that outcome measures were consequently employed and used on a frequent basis aiming to achieve quality improvement in healthcare. Results can be improved by structurally embedding the entire improvement cycle into the organisation.